AI-facilitated coating corrosion assessment system for productivity enhancement - Liu, Lili; Tan, Estee; Zhen, Yongda; Yin, Xi Jiang; Cai, Zhi Qiang (IEEE Conference on Industrial Electronics and Applications (Online), 2018)
Application of protective coatings is the primary method used to protect marine and offshore structures from coating breakdown and corrosion (CBC). Assessment of CBC is the major aspect in coating failure management. Subjective assessment methods cause unnecessary maintenance cost and higher risk of failure. To improve efficiency and productivity, an integrated coating breakdown and corrosion (CBC) assessment system is developed. This AI-facilitated CBC inspection system implements a deep transfer learning technique to automate CBC assessment, it includes a faster region-base convolutional neural network (faster R-CNN) architecture and a vgg19 model for deep transfer learning, an instance-aware semantic segmentation method is developed for CBC measurement and grading. This method provides efficient inspection techniques for marine and offshore industries.